Werkstofflicher Ansatz zum adhäsiv-basierten Fügen für hochflexible TPE-Organobleche als Verstärkungsstruktur - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Influence of the processing parameters on the mechanical strenght of injection moulded BMC components for direct screwing - Held, Christian; Moritzer, Elmar (the 40th International Conference of Polymer Processing Society)

Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Experimentelle Ermittlung von Rissablenkungswinkeln bei außerphasiger Mixed-Mode-Belastung mittels einer neuartigen Probengeometrie - Weiß, Deborah; Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Ostwald, Richard

Vergleich experimenteller Methoden zur Untersuchung des Aufschmelzprozesses in Einschneckenextrudern - Knaup, Felix; Brüning, Florian (Extrusion)
Keywords: Aufschmelzen; extrusion; Messtechnik

Disentangling Negative Sentiment towards Virtual Influencers: Towards a Taxonomy of Criticism - Tölle, Laura; Rehmer, Torben; Müller, Johann; Ruppel, Fynn; Trier, Matthias

Using ChatGPT for Identifying Negative Structures in Social Media Conversations - Tölle, Laura; Nolting, Max; Trier, Matthias

Method for systematic creation of test scenarios for early customer involvement - Gräßler, Iris; Ebel, Marcel; Pottebaum, Jens (Procedia CIRP)
Verification planning for engineering complex systems lacks a systematic procedure for creating test scenarios. Test scenarios can be generated by combining test cases, or by integrating test cases into pre-specified scenarios. Based on a systematic literature analysis a method is developed to simplify verification planning by creating new test scenarios and enriching existing ones. To assist the V&V engineer in planning test scenarios, a catalogue of combination premises is created to support the method. The method is evaluated in the development of a platform for emergency management. Evaluation proves that the method makes modelling of test scenarios more efficient.
Keywords: Systems Engineering; test scenario creation; verification; customer involvement

Ganzheitliches Metadatenmodel für die Verifikation und Validierung in der Entwicklung komplexer technischer Systeme - Gräßler, Iris; Ebel, Marcel (DS 140: Proceedings of the 36th Symposium Design for X (DFX2025))
The increasing complexity of technical systems requires early, structured verification and validation (V&V). Existing metadata models only map parts of the engineering process and do not enable a continuous chain of effects from requirements to test results. The aim of this publication is to develop a holistic V&V metadata model for the consistent, transparent and machine-processable description and linking of relevant engineering artifacts. In a five-stage research approach, essential model components are derived from literature and are integrated into a holistic model. Initial applications as part of a European research project show the potential of the model for a well-founded effect chain analysis and decision-supporting V&V processes.
Keywords: verification; metadata model; Systems Engineering

Augmented Reality for Navigation, Team Coordination, and Real-Time Data Visualization in Firefighting Operations - Charalampakis, Konstantinos; Safranoglou, Ioannis; Stavroulakis, Alexis; Ebel, Marcel; Gräßler, Iris; Dimelli, Despina; Mania, Katerina (2025 IEEE International Symposium on Mixed and Augmented Reality Adjunct (ISMAR-Adjunct))

Thermo-Chemical Devulcanization of Sulfur-Cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Schöppner, Volker

Symmetry as a Topic for the University Education of Pre-Service Teachers - Hoffmann, Max (Recherches en Didactique des Mathématiques)
This article provides a comprehensive mathematical-didactic analysis of how the highly relevant topic symmetry can be prepared for the university education of PSTs. Methodologically, the analysis is embedded in a design research cycle and serves as preparation for the actual design of learning activities. The procedure of "specifying and structuring" learning objects is used and adapted in such a way that, in addition to mathematical aspects, profession-oriented references to school mathematics are also considered. An essential result of the analysis is the formulation of so-called interface aspects to symmetry, which prove to be helpful in establishing such references.

Influence of Filler Type and Volume Fraction on the Electrical Conductivity and Shore Hardness of TPU Composites in Fused Filament Fabrication - Moritzer, Elmar; Salm, Maximilian Karl Franz (The 40th International Conference of Polymer Processing Society)

Using scriptwriting as a response format for interface tasks: Exemplary analyses in the context of symmetry - Hoffmann, Max (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14))

Non-destructive fiber-matrix adhesion measurement of glass fiber reinforced thermoplastic composite laminates using ultrasound - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Henning, Bernd (40th International Conference of the Polymer Processing Society)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Experimental Analysis of the Mixing Behavior of Ethylene-Propylene-Diene Rubber (EPDM) in a Rubber Pin Extruder under Variation of Process Parameters and Mixing Elements - Petzke, Jonas Dirk Rudolf Helmut; Schmidt, Leon; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: distributives Mischen; Extrusion; Kautschuk; Stiftextruder

Numerical modeling of the non-isothermal viscoelastic flow behavior of rubber compounds based on the PHAN-THİEN-TANNER (PTT) model - Damanik, Hogenrich; Fatima, Arooj; Turek, Stefan; Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: CFD simulation; Materialmodellierung; Phan-Thien-Tanner; PTT; Simulation

Thermo-Chemical Devulcanization of Sulfur-cured Styrene-Butadiene Rubber (SBR) Using Diphenyldisulfide (DPDS) - Petzke, Jonas Dirk Rudolf Helmut; Kleinschmidt, Dennis; Brüning, Florian (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: Devulkanisation; Kautschuk; Recycling